Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.5430/ijh.v3n2p78
|View full text |Cite
|
Sign up to set email alerts
|

The healthcare system in Saudi Arabia: How can we best move forward with funding to protect equitable and accessible care for all?

Abstract: The Saudi Arabian healthcare system is currently undergoing a process of reform. While it previously adopted a universal access approach in which all health care was provided free-of-charge to citizens at the point of care, this has been identified as unsustainable into the future. The shift towards an ageing population and the increasing burden of chronic disease, along with increasing use of technology and development of expensive treatments, mean that health care costs in Saudi Arabia are likely to increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…The possible reason for this could be that more highly educated people have a greater awareness of health‐related issues and have better health‐seeking behaviours compared with less well‐educated participants . Despite the fact that the health care services in the KSA are provided free at the point of use, the study found that the prevalence of diabetes was concentrated among poorer people. Poorer people might not be able to afford proper diet and health care services, thereby affecting their access and health‐seeking behaviours such as transport or travel expenses and even absence from work .…”
Section: Discussionsupporting
confidence: 84%
“…The possible reason for this could be that more highly educated people have a greater awareness of health‐related issues and have better health‐seeking behaviours compared with less well‐educated participants . Despite the fact that the health care services in the KSA are provided free at the point of use, the study found that the prevalence of diabetes was concentrated among poorer people. Poorer people might not be able to afford proper diet and health care services, thereby affecting their access and health‐seeking behaviours such as transport or travel expenses and even absence from work .…”
Section: Discussionsupporting
confidence: 84%
“…The present situation appears unsustainable in the medium to long term, especially with uncertainties regarding oil prices. The future viability of the current healthcare financing system has therefore been questioned by both academics and international health organizations [ 8 – 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Private health services are expanding, and are envisioned under Vision 2030 to support the public infrastructure . Under Vision 2030, the strategy will be to improve and expand healthcare to meet the needs of the population, while incorporating features and services from the private sector strategically, such as private sector health insurance . While the healthcare system is well‐developed and represents a benefit to the population, those with low HL stand to be at higher risk for lack of access to healthcare and healthcare‐associated morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%